Synthesis and Characterization of Gold Nanoparticles and Gold Nanoparticles Loaded with Bromelain - Haneen Ibrahim Ali; Baydaa H. Mutlak (Iraqi Journal of Physics)
The production and use of nanometallic elements, such as gold, have received a lot of attention lately due to their distinctive features and wide range of uses. Most of these studies have employed the Turkevich approach. This research employed the Turkevich technique to produce gold nanoparticles (AuNPs). AuNPs and bromelain-loaded AuNPs were characterised using a variety of methods, including ultraviolet-visible spectroscopy (UV-Vis), Fourier transform infrared spectroscopy (FTIR), field emission scanning electron microscopy (FE-SEM), X-ray diffraction (XRD), transmission electron microscopy (TEM), and zeta potential (ZP) measurements. The UV-Vis spectra of Bromelain, AuNPs, and AuNPs-Bromelain each had a peak at 276, 534, and 550 nm wavelengths, respectively. The FE-SEM and TEM studies revealed the presence of spherical particles with a smooth surface. The diameters of the AuNPs ranged from 49.32 to 77.29 nm; the diameters of the Bromelain-AuNPs ranged from 46.39 to 75.66 nm, as determined by the FE-SEM analysis. The TEM analysis indicated that the particles' sizes ranged from 7.40 to 15 nm for AuNPs and 14.51 nm for AuNPs-Bromelain. The XRD patterns revealed numerous diffraction peaks, indicating the crystal structure of the synthesised nanoparticles. FTIR spectrometry was employed to identify the functional groups in the synthesised nanoparticles. Zeta potential (ZP) measurements revealed that AuNPs had a zeta potential value of +0.1±0.4, and the zeta potential value for AuNPs-Bromelain was +1.2±3.0 mV.